2008
DOI: 10.1007/s10869-008-9086-9
|View full text |Cite
|
Sign up to set email alerts
|

Recruiters’ Inferences of Applicant Personality Based on Resume Screening: Do Paper People have a Personality?

Abstract: Research shows recruiters infer dispositional characteristics from job applicants' resumes and use these inferences in evaluating applicants' employability. However, the reliability and validity of these inferences have not been empirically tested. Using data collected from 244 recruiters, we found low levels of estimated interrater reliability when they reviewed entry-level applicants' resumes and made inferences regarding applicants' personality traits. Moreover, when recruiters' inferences of applicant pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
99
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 56 publications
(97 reference statements)
7
99
3
1
Order By: Relevance
“…They found recruiter Implications of personality traits in business graduates judgement on personality traits was typically inaccurate and unreliable, with accurate inferences occurring only for Extroversion, this being more transparent through, for example, the number of extra-curricular activities, confirmation of the broad acknowledgement of its high visibility in the context of recruitment. Despite expectations that Consciousness and Openness would be transparent in resumés via strong academic achievement and an interest in diverse activities such as travel and community activities, the findings of Cole et al (2009) suggested otherwise. Interestingly, their study indicated that business graduates perceived to have higher levels of Conscientiousness, Extroversion and Openness received more positive employability assessments in the initial stages of screening.…”
Section: Personality and Graduate Selectionmentioning
confidence: 74%
“…They found recruiter Implications of personality traits in business graduates judgement on personality traits was typically inaccurate and unreliable, with accurate inferences occurring only for Extroversion, this being more transparent through, for example, the number of extra-curricular activities, confirmation of the broad acknowledgement of its high visibility in the context of recruitment. Despite expectations that Consciousness and Openness would be transparent in resumés via strong academic achievement and an interest in diverse activities such as travel and community activities, the findings of Cole et al (2009) suggested otherwise. Interestingly, their study indicated that business graduates perceived to have higher levels of Conscientiousness, Extroversion and Openness received more positive employability assessments in the initial stages of screening.…”
Section: Personality and Graduate Selectionmentioning
confidence: 74%
“…While resumes and applications provide much factual and verifiable information such as educational achievements, certifications, licenses, experience, and so on, employers also use them to infer other characteristics such as personality, intelligence, leadership, and work ethic (Cable & Gilovich, 1998;Cole, Feild, Giles, & Harris, 2009). They then use these inferences to assess prospect employability (Brown & Campion, 1994;Cole, Feild, & Giles, 2003;Cole, Rubin, Feild, & Giles, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Typical studies have focused on the role of résumés in applicant screening in the preinterview phase in relation to invitations to subsequent employment interviews (Brown and Campion 1994;Chen et al 2011;Cable and Gilovich 1998;Cole et al 2007Cole et al , 2009Johnson and Lahey 2011;Thoms et al 1999;Tsai et al 2011). Despite studies exploring the relative importance of recruiters' preinterview evaluations of or knowledge of résumé information and applicants' interview performance in postinterview decision making (Kinicki et al 1990;Dalessio and Silverhart 1994;Macan and Dipboye 1990;Wade and Kinicki 1995), the inconsistent findings drawn from these studies failed to clarify the respective roles of information-utilizing mechanisms in the preinterview and interview phases of the selection process.…”
mentioning
confidence: 99%
“…As the industry provides the labor market with a considerable amount of entry-level job vacancies (Kusluvan et al 2010;Okumus et al 2010), screening applicants by evaluating résumés and then proposing a list of recommended candidates to interviewers for subsequent interviews to assess candidates' attributes is a more economic employment practice (Cole et al 2009;Hutchinson 1984). Accordingly, how effectively recruiters infer applicants' qualifications from résumés matters because their recommendations influence organizations' hiring decisions (Cole et al 2009). We propose that there is difference in effect size across preinterview judgments on postinterview acceptance decision making.…”
mentioning
confidence: 99%
See 1 more Smart Citation